Spread me [large type] - Gailey, Sarah (Thorndike Press large print high octane., 2025)
"Spread Me is a darkly seductive tale of survival from Sarah Gailey, bestselling author of Just Like Home. A routine probe at a research station turns deadly when the team discovers a strange specimen in search of a warm place to stay. Kinsey has the perfect job as the team leader in a remote research outpost. She loves the isolation and the way the desert keeps temptations from the civilian world far out of reach. When her crew discovers a mysterious specimen buried deep in the sand, Kinsey breaks quarantine and brings it into the hab. But the longer it's inside, the more her carefully controlled life begins to unravel. Temptation has found her after all, and it can't be ignored any longer. One by one, Kinsey's team realizes the thing they're studying is in search of a new host-and one of them is the perfect candidate..."-- Provided by publisher.